Paint the wind - Ryan, Pam Muñoz (Scholastic Inc., 2009)
Young Maya lives a lonely life in her grandmother's house in California, but things soon change for Maya when she discovers that Artemisia, a wild horse in Wyoming, holds the key to her memories of her mother.